Supervisi Akademik oleh Wakil Kepala Madrasah Bidang Kurikulum dalam Meningkatkan Kinerja Guru - Parhati, Dewi (Journal of Innovation in Teaching and Instructional Media, 2022)
In carrying out academic supervision, the role of a deputy head of the curriculum is needed. The purpose of this study was to dig up information about the role of the vice principal in the curriculum field at MTs Negeri 1 Prabumulih in order to develop the ability of teachers to arrange assessment administration through academic supervision. This study uses a qualitative method. Data were collected through interviews, observation, and documentation. The subjects in this study were the Deputy Head of Madrasah in the field of curriculum and teachers. The results showed that: 1) madrasa academic supervision program planning was prepared at the beginning of each new school year; 2) the implementation of academic supervision includes class visits, and observations; 3) the deputy head of the madrasa in the field of curriculum carries out the supervision assessment process for teachers; 4) the implementation of academic supervision has a real impact on improving teacher performance at MTs Negeri 1 Prabumulih City.